2006
DOI: 10.1590/s1806-37132006001300008
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<B>Impact of open lung biopsy on refractory acute respiratory failure</B>]]>

Abstract: We conclude that open lung biopsy is a useful tool in the management of acute respiratory failure when there is no clinical improvement after standard treatment, since it can lead to a specific diagnosis that requires distinct treatment, which probably lowers the mortality rate among such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Patient mortality (defined variably as hospital, intensive care unit, or 28-30 days after open lung biopsy) was 54%. Mortality rates stratified by histopathological diagnosis did not differ significantly by diagnosis (P = 0.15; Table 2, reported in eight studies) (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Systematic Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Patient mortality (defined variably as hospital, intensive care unit, or 28-30 days after open lung biopsy) was 54%. Mortality rates stratified by histopathological diagnosis did not differ significantly by diagnosis (P = 0.15; Table 2, reported in eight studies) (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Systematic Reviewmentioning
confidence: 95%
“…Therapy was discontinued in 10% (n = 39, 95% CI, 7-13%) of patients. Two studies (20 patients, 5%) did not report therapeutic changes (4,5).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Until now, no reports of OLB findings used to guide the treatment of patients with H1N1 pneumonitis have been published, although according to many authors OLB is safe and diagnostically useful in patients with ARF, enabling appropriate therapy. [9][10][11][12] The pathogenesis of ARF associated with swine-origin influenza virus (S-OIV) infection in humans is unknown. The influenza virus triggers pulmonary inflammation owing to an infiltration of inflammatory cells and an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic yield of OLB, which does not specifically address solid organ transplant patients, ranges between 34% and 100% (16,17,19,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In solid organ transplant patients, Defranchi et al reported that 29% had a change in clinical management as a result of the OLB findings (16).…”
Section: Discussionmentioning
confidence: 99%